Functional characterization of cannabidiol effect on the serotonergic neurons of the dorsal raphe nucleus in rat brain slices - Mendiguren, Aitziber; Aostri, Erik; Alberdi, Elena; Pérez-Samartín, Alberto; Pineda, Joseba (Frontiers in Pharmacology, 2022)
Cannabidiol (CBD), the main non-psychoactive cannabinoid found in the cannabis plant, elicits several pharmacological effects via the 5-HT1A receptor. The dorsal raphe nucleus (DRN) is the main serotonergic cluster in the brain that expresses the 5-HT1A receptor. To date, the effect of CBD on the neuronal activity of DRN 5-HT cells and its interaction with somatodendritic 5-HT1A autoreceptors have not been characterized. Our aim was to study the effect of CBD on the firing activity of DRN 5-HT cells and the 5-HT1A autoreceptor activation by electrophysiological and calcium imaging techniques in male Sprague–Dawley rat brain slices. Perfusion with CBD (30 μM, 10 min) did not significantly change the firing rate of DRN 5-HT cells or the inhibitory effect of 5-HT (50–100 μM, 1 min). However, in the presence of CBD (30 μM, 10 min), the inhibitory effects of 8-OH-DPAT (10 nM) and ipsapirone (100 nM) were reduced by 66% and 53%, respectively. CBD failed to reverse ipsapirone-induced inhibition, whereas perfusion with the 5-HT1A receptor antagonist WAY100635 (30 nM) completely restored by 97.05 ± 14.63% the firing activity of 5-HT cells. Administration of AM251 (1 µM), MDL100907 (30 nM), or picrotoxin (20 μM) did not change the blockade produced by CBD (30 μM) on ipsapirone-induced inhibition. Our study also shows that CBD failed to modify the KCl (15 mM, 4 min)-evoked increase in [Ca2+]i or the inhibitory effect of ipsapirone (1 μM, 4 min) on KCl-evoked [Ca2+]i. In conclusion, CBD does not activate 5-HT1A autoreceptors, but it hindered the inhibitory effect produced by selective 5-HT1A receptor agonists on the firing activity of DRN 5-HT cells through a mechanism that does not involve CB1, 5-HT2A, or GABAA receptors. Our data support a negative allosteric modulation of DRN somatodendritic 5-HT1A receptor by CBD.